Caracterización fenotípica de la cabra criolla y su sistema de producción, en la parroquia Limones del cantón Zapotillo - Flores González, Alex Maximiliano (2018)
This research work was developed in the Limones parish of Zapotillo canton, located 22 km from the cantonal capital, with the purpose of phenotypically characterizing the Creole goat and the production system in which it is being exploited. to determine the productive, reproductive and zoomometric parameters, once obtained the same socialize them with the actors involved in the goat sector. We used 14 goat herds, with a number of 86 animals under study within them, with a weight of 33-39 kg in adulthood; Two visits were made to the herds with an average interval of 70 days between the first and second visits. For the phenotypic characterization, zoometric measurements were taken as phaneroptic, to determine its production system, a goat producer survey was carried out, in the same way to establish the productive and reproductive parameters. The results that were found to the racial bio-type of the Creole goat of the parish Limones is of a small stature goat (62-65 cm height at the withers), of short body length (61-68 cm), of face profile straight (83.7%), with short horns (71%) and long horns (29%) in the form of a saber, straight and short ears (80%), with a fur attached to the body (92%) in the same that predominate two main layers black and brown, with irregular spots throughout the body, with a globose udder (88%), presence of sarcillos (15%), short nipples (2,2 cm) and pigmented (86%) as well as the hooves, with a width of chest of 15-16 cm, its average daily gain in extensive conditions is low, but it has a great ability to adapt and survive in extreme conditions where it develops, of low milk production, with values ​​of 0 , 5 liters / day / animal, with a duration of lactation of approximately 30 days, with a labor-estrus interval of approximately 103 days. For the values ​​obtained here it is recommended the preservation of the Creole resource and the continuity of research work on it. Key words: phenotypically, parameters, zoometrics, goats, interval, characterization, spots, globose.